2014
DOI: 10.1007/s11606-014-3014-7
|View full text |Cite
|
Sign up to set email alerts
|

Midodrine Efficacy in Orthostatic Hypotension

Abstract: feel obligated to comment on several deficiencies of this work. Unfortunately, the article was published under the Mayo Clinic name by former trainees without expert supervision, since none of the autonomic experts at Mayo who author this letter were in any way involved in conducting the study or guiding its interpretation. The deficiencies are major and reflect poorly on Mayo Clinic investigators. Furthermore, this article needs rectification-both of content and interpretation-to avoid potential damage to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…When α 1 -AR is activated by midodrine in clinical practice, it is safe, and side effects are rare [39]. Regarding the dose of midodrine required to have a metabolic effect, we found a significant increase in p-AMPK, PPARδ, and PGC-1α expression in C2C12 myocytes following treatment with as little as 3 μM midodrine.…”
Section: Ppar Researchmentioning
confidence: 81%
“…When α 1 -AR is activated by midodrine in clinical practice, it is safe, and side effects are rare [39]. Regarding the dose of midodrine required to have a metabolic effect, we found a significant increase in p-AMPK, PPARδ, and PGC-1α expression in C2C12 myocytes following treatment with as little as 3 μM midodrine.…”
Section: Ppar Researchmentioning
confidence: 81%
“…There are some differences between the effects we observed in C. elegans and those in mammalian models, which may be due to the fact that the C. elegans NHR-49 acts in a similar manner to PPAR-α [ 52 ], and the PPAR found to be most responsive to Midodrine in humans was PPAR-γ(50). As Midodrine activates α1-Adrenergic Receptors and has been shown to have few side effects [ 53 ], this is a second likely candidate in the arsenal against obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Midodrine does have FDA approval for treatment of orthostatic hypotension. Because of effects from desglymidorine on arterial and venous constriction, midodrine raises both supine and standing blood pressure with minimal to no effects of narrowing the fall in orthostatic blood pressure [47]. A recent systemic review on efficacy of midodrine in patients with symptomatic orthostatic hypotension and recurrent reflex syncope showed that midodrine may have positive benefits for clinical outcome without [53].…”
Section: Midodrinementioning
confidence: 99%